Early nutritional intervention can improve utilisation of vegetable-based diets in diploid and triploid Atlantic salmon (Salmo salar L.). Issue 1 (24th July 2017) - Clarkson, Michael; Migaud, Herve; Metochis, Christoforos; Vera, Luisa M.; Leeming, Daniel; Tocher, Douglas R.; Taylor, John F.
Abstract: The present study investigated nutritional programming in Atlantic salmon to improve utilisation of a vegetable-based diet. At first exogenous feeding, fry were fed either a marine-based diet (Diet M stimulus, 80% fishmeal (FM)/4% fish oil (FO)) or a vegetable-based diet (Diet V stimulus, 10% FM/0% FO) for 3 weeks. Subsequently, all fish were then fed under the same conditions with a commercial, marine-based, diet for 15 weeks and thereafter challenged with a second V diet (Diet V challenge, 10% FM/0% FO) for 6 weeks. Diploid and triploid siblings were run in parallel to examine ploidy effects. Growth performance, feed intake, nutrient utilisation and intestinal morphology were monitored. Fish initially given Diet V stimulus (V-fish) showed 24 % higher growth rate and 23 % better feed efficiency compared with M-fish when later challenged with Diet V challenge . There was no difference in feed intake between nutritional histories, but increased nutrient retentions highlighted the improved utilisation of a V diet in V-fish. There were generally few significant effects of nutritional history or ploidy on enteritis scores in the distal intestine after the challenge phase as only V-triploids showed a significant increase ( P <0·05) in total score. The data highlighted that the positive effects were most likely a result of nutritional programming and the ability to respond better when challenged later in life may be attributed to physiological and/or metabolic changes induced by the stimulus. This novel study showed the potential of nutritional programming to improve the use of plant raw material ingredients in feeds for Atlantic salmon.